NEED ACCESSMENT OF CONTEXTUAL-BASED PHYSICS LEARNING VIDEO SUBJECT MATTER TEMPERATURE AND CALOR FOR 21ST CENTURY LEARNING - Sadra Hamida; Desnita Desnita (Universitas Negeri Medan, 2020)
Primary analysis is a very important stage in a research development. Because the information obtained from this activity is the reason for the development of a research product. A preliminary study has been conducted in 7 high schools in West Sumatra, which aims to obtain information about the character of students, media and learning resources used by high school physics teachers to teach temperature and heat. This study was carried out in order to see the compatibility between the media and learning resources used by physics teachers with learning needs in the 21st Century. This activity applies a survey method, using questionnaire. Based on the analysis of student characteristics that have been obtained, students' interest in learning physics is 74.28, attitude is 76.29, student motivation is 79.36 and student learning style is 78.16. Initial analysis of teaching materials and media used by teachers obtained 100% of teachers stated that using textbooks in the learning process, 12.5% of teachers use modules and encyclopedias, 62.5% of teachers use LKS in the learning process. Learning media used by teachers in schools 37.5% teachers use videos, 37.5% teachers use power points. These results indicate that students' interest and motivation to learn are good, but the media used still needs to be adjusted. One of them is the addition of learning videos